2015
DOI: 10.1089/end.2014.0413
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pectopexy: A Prospective, Randomized, Comparative Clinical Trial of Standard Laparoscopic Sacral Colpocervicopexy with the New Laparoscopic Pectopexy—Postoperative Results and Intermediate-Term Follow-Up in a Pilot Study

Abstract: Laparoscopic pectopexy is a novel method of vaginal prolapse therapy that offers clear practical advantages compared with laparoscopic sacropexy. Because laparoscopic pectopexy does not reduce the pelvic space, it results in a zero percentage of defecation disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 23 publications
5
69
1
3
Order By: Relevance
“…Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee . In the LLS technique group, objective cure rates at the 1‐year follow‐up were 91.6% for the anterior, 93.6% for the apical, and 85.3% for the posterior compartment …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee . In the LLS technique group, objective cure rates at the 1‐year follow‐up were 91.6% for the anterior, 93.6% for the apical, and 85.3% for the posterior compartment …”
Section: Resultsmentioning
confidence: 64%
“…The concept of reconstructive repair includes both restoration of the descending compartment and preventive correction of unaffected compartments . In the studies analyzed in this review, surgery was often accompanied by concomitant procedures for other compartments and/or anti‐incontinence surgery, which lowered the risk of reoperation . These additional repairs contribute to the overall success of surgery and should be considered accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study can be assigned to stage 1 of IDEAL-system. Another singlecenter randomized prospective clinical trial presented data on laparoscopic bilateral fixation of the vagina/cervix to the iliopectineal ligaments via a PVDF-mesh in 44 patients versus 41 standard laparoscopic sacropexies with PVDF-mesh [24]. The intermediateterm follow-up (21.8 months for pectopexy and 19.5 months for sacropexy) showed no mesh-related adverse events with high overall satisfaction (>95%).…”
Section: Discussionmentioning
confidence: 99%